KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KANTOR DISTRIK MERAUKE - Andri Irawan; Farida Romaito Pohan; Susana P.Y Fofid (Universitas Islam Darul Ulum Lamongan, 2021)
This study aims to determine the quality of population administration services at the Merauke District Office, which includes services for making Family Cards (KK), birth certificates, marriage certificates, death certificates, certificates of moving in and out of residents. The method in this research uses a qualitative approach. This study uses data analysis techniques consisting of data reduction, data presentation and conclusion drawing. The results showed that the quality of population administration services at the Merauke District Office was seen from the indicators of the quality of public services; (1) physical evidence is sufficient in providing services to the community, it can be seen from the new service waiting room, comfortable and spacious and equipped with air conditioning, but there is still a lack of filling cabinets and suggestion boxes. (2) the aspect of reliability, employees in responding to any service complaints have not been in accordance with the expectations and desires of the community, as can be seen from the complaints from the public about the population administration service process. (3) the responsiveness aspect of employees has shown a responsive attitude in helping the community when experiencing difficulties in the process of making family cards (KK), birth certificates, marriage certificates, death certificates and residence certificates. (4) the aspect of guarantee, the accuracy of the guarantee on time of service is still not in accordance with the expectations of the community, it can be seen that there are still complaints from the community related to the timeliness of the service process. (5) the aspect of empathy, the Merauke District office has shown efforts to improve service quality, namely by giving a good impression in the service process. The factors that hinder the service process at the Merauke District Office include the lack of human resources or employees, public awareness in completing administrative requirements, and the need for the addition of several facilities such as filing cabinets for documents and suggestion boxes.